Reliability and clinical utility of the chronic pain classification in the 11th Revision of the International Classification of Diseases from a global perspective: results from India, Cuba, and New Zealand : research paper - Korwisi, Beatrice; Garrido Suárez, Bárbara Beatriz; Goswami, Subrata; Gunapati, Nischala Reddy; Hay, Ginea; Hernández Arteaga, Manuel Angel; Hill, Charlotte; Jones, David; Joshi, Muralidhar; Kleinstäuber, Maria; López Mantecón, Ana Marta; Nandi, Gargi; et al. (Pain, 2022)
Chronic pain affects 1 in 5 persons and contributes substantially to the global burden of disease. The 11th Revision of the International Classification of Diseases (ICD-11) includes a comprehensive classification of chronic pain. The aim of this ecological implementation field study was to evaluate the classification's interrater reliability and clinical utility in countries with different income levels. The study was conducted in 4 pain clinics in Cuba, India, and New Zealand. Twenty-one clinicians used the ICD-11 to diagnose and code n = 353 patients with chronic pain. Of these, 111 were assessed by 2 clinicians, and Fleiss' kappa was calculated to establish interrater reliability for any diagnosis assigned to ≥15 patients. The clinicians rated the clinical utility of all diagnoses. The interrater reliability could be calculated for 11 diagnoses. It was substantial for 10 diagnoses and moderate for 1 (kappa: 0.596-0.783). The mean clinical utility of the ICD-11 chronic pain diagnoses was rated as 8.45 ± 1.69/10. Clinical utility was rated higher for ICD-11 than for the commonly used classification systems (P < 0.001, η2 = 0.25) and differed between all centers (P < 0.001, η2 = 0.60). The utility of the ICD-11 diagnoses was rated higher than the commonly used diagnoses in Dunedin and Havana, and no difference was found in Kolkata and Hyderabad. The study showed the high interrater reliability of the new chronic pain diagnoses. The perceived clinical utility of the diagnoses indicates their superiority or equality compared with the classification systems currently used in pain clinics. These results suggest the global applicability of the classification in specialized pain treatment settings.
Gesehen am 29.04.2024